Dietary patterns at 7 year-old and their association with cardiometabolic health at 10 year-old - Pinto, A (2020)
Background & aims: Diet is usually represented as single foods or dietary patterns not related with a specific outcome, and its cardiometabolic effects at early ages are not clearly understood. This study aims to assess whether dietary patterns derived at 7 years of age have an effect on cardiometabolic health at 10 year-old. Methods: This study uses data from the Generation XXI birth cohort (northern Portugal, 2005–2006). Dietary data were collected by a validated food frequency questionnaire at 7 year-old and dietary patterns were previously derived through partial least squares (PLS), principal component analysis and latent class analysis. At 10 year-old, systolic (SBP) and diastolic (DBP) blood pressure were measured, and blood samples were drawn to analyze cardiometabolic parameters. Linear regression coefficients and 99% confidence intervals [βˆ (99% CI)] were computed (covariates: birth weight, gestational age, physical activity, maternal age and education) (n = 3350). Results: A dietary pattern that explains the BMI z-score at 10 year-old (PLS-1, characterized by the intake of processed meat, energy-dense foods and low in vegetables) was significantly associated with SBP (βˆ = 0.052, 99% CI:0.022; 0.082), DBP (βˆ = 0.043, 99% CI: 0.022; 0.065), triglycerides (βˆ = 0.065, 99% CI: 0.026; 0.104), HDL-cholesterol (βˆ = −0.059, 99% CI: −0.099; −0.019), LDL-cholesterol (βˆ = 0.040, 99% CI: 0.001; 0.080) and HOMA-IR (βˆ = 0.110, 99% CI: 0.071; 0.149). After further adjustment for BMI at 10 year-old, the magnitude of the associations was weakened. No associations were observed between the other derived dietary patterns and cardiometabolic health. Conclusions: Adherence at 7 years of age to a dietary pattern rich in energy-dense foods, processed meat and low in vegetables, may increase several cardiometabolic parameters at 10 years of age. BMI at 10 year-old explained part of these effects.